Docking Study to Predict the Efficacy of Phosphatidylinositol 3-Kinase α Inhibitors - Chawsheen, Mahmoud A.; Al-Bustany, Hazem A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
The phosphatidylinositol 3-kinase (PI3K) family comprises lipid kinases that cross-link signals between living cells and their surroundings. PI3Ks are classified into several groups and isoforms with specific characteristics and functions. Genes encoding PI3Ks are mutated in several types of cancer, and their isoforms have varying capacity in promoting cell signaling and cancer progression. Many compounds have been introduced as PI3Kα inhibitors, but not all of them have the same inhibitory effects. For successful PI3K-related biomedical experiments, it is vital to select the most specific and potent compounds with the highest inhibitory effects for targeting this kinase. In this study, we investigate 28 well-recognized PI3Kα inhibitors through predicting their specificity and potency using the docking software AutoDock Vina. Our data showed that PF 05212384 had the highest docking score (−9.2 kcal/mol), and 3-methyladenine had the lowest docking score (−4.8 kcal/mol). Our data also showed different types of interactions and bonds formed between the inhibitors and protein residues. In conclusion, PF 05212384 and AZD 6482 compounds are the best candidates for targeting PI3Kα. In addition to hydrophobic interactions in the PI3Kα binding pocket, the formation of hydrogen bonds between these inhibitors and binding pocket residues was confirmed.